An LC-MS/MS method for creatine and creatinine analysis in paraquat-intoxicated patients. Issue 3 (3rd March 2020) - Sukhang, Mukdawan; Junkuy, Anongphan; Buckley, Nicholas; Mohamed, Fahim; Wunnapuk, Klintean
Abstract: A sudden increase in serum creatinine after paraquat intoxication has been reported in several clinical studies. However, this dramatic change of creatinine may be possibly due to an interconversion of creatine-creatinine in relation to paraquat toxicity. In order to investigate the creatine-creatinine relationship, a liquid chromatography tandem mass spectrometry in combination with electrospray ionization was developed and validated for simultaneous determination of creatine and creatinine in the serum. The chromatographic separation was achieved on a Gemini® C6 -Phenyl column with a gradient elution consisting of 0.1% formic acid in ultrapure water and methanol as the mobile phase. The method yielded suitable levels of specificity and selectivity, and calibration curves of creatine and creatinine in serum were linear over the concentration range of 0.5–200 µg mL −1 . The limit of quantification of both compounds was 0.5 µg mL −1, and the method was accurate within the recovery range of 96.23–102.75%, indicating the robustness of the method. The method was successfully applied to toxicological samples from paraquat-intoxicated patients, and the concentrations of creatine and creatinine were quantified. High creatine concentrations in serum samples were observed which may lead to high serum creatinine despite normal kidney function as creatine is converted to creatinine in proportion to its concentration.